Multifactorial risk factors for hospital readmissions among patients with symptoms of advanced heart failure - Chetna Malhotra; Isha Chaudhry; Yeo Khung Keong; Kheng Leng David Sim (ESC Heart Failure, 2024)
Abstract Aims Economic burden of heart failure is attributed to hospital readmissions. Previous studies assessing risk factors for readmissions have focused on single group of risk factors, were limited to 30‐day readmissions, or did not account for competing risk of mortality. This study investigates the biological, socio‐economic, and behavioural risk factors predicting hospital readmissions while accounting for the competing risk of mortality. Methods and results In this prospective cohort study, we recruited 250 patients hospitalized with symptoms of advanced heart failure [New York Heart Association (NYHA) Class III and IV] between July 2017 and April 2019. We analysed their baseline survey data and their hospitalization records over the next 4.5 years (July 2017 to January 2022). We used a joint‐frailty model to determine the multifactorial risk factors for all‐cause and unplanned hospital readmissions and mortality. At the time of recruitment, patients' mean (SD) age was 66 (12) years, majority being male (72%) and NYHA class IV (68%) with reduced ejection fraction (72%). 87% of the patients had poor self‐care behaviours, 51% had diabetes and 56% had weak grip strength. Within 2 years of a hospital admission, 74% of the patients had at least one readmission. Among all readmissions during follow‐up, 68% were unplanned. Results from the multivariable regression analysis shows that the independent risk factors for hospital readmissions were biologic—weak grip strength [hazard ratio (95% CI): 1.59 (1.06, 2.13)], poor functional status [1.79 (0.98, 2.61)], diabetes [1.42 (0.97, 1.86)]; behavioural—poor self‐care [1.66 (0.84, 2.49)], and socio‐economic—preference for maximal life extension at high cost for those with high education [1.98 (1.17, 2.80)]. Risk factors for unplanned hospital readmissions were similar. A higher hospital readmission rate increased the risk of mortality [1.86 (1.23, 2.50)]. Other risk factors for mortality were biologic—weak grip strength [3.65 (0.57, 6.73)], diabetes [2.52 (0.62, 4.42)], socio‐economic—lower education [2.45 (0.37, 4.53)], and being married [2.53 (0.37, 4.69)]. Having a private health insurance [0.40 (0.08, 0.73)] lowered the risk for mortality. Conclusions Risk factors for hospital readmissions and mortality are multifactorial. Many of these factors, such as weak grip strength, diabetes, poor self‐care behaviours, are potentially modifiable and should be routinely assessed and managed in cardiac clinics and hospital admissions.